Victor Grant Collection, Album 5, Photograph 284 1910 Cowboy Dance at Cimarron, New Mexico
Front row left: Katie (Lambert). Center sitting, Fred (Lambert).
Designation 5.284 in listing stands for Album 5, Photograph 284
From collection of photographs compiled by Victor Grant, descendant of the Maxwell / Beaubien family.
Located in Office Closet
Keywords: Lambert, Fred; Lambert, Katie; Lambert family. -- New Mexico; Genealogy - Photographic collection